An antifouling coating with anticoagulation and / or in situ endothelialization function and its preparation method and application
Through basal activation and carbon-carbon double-bond silicone modification, the antifouling molecular density is regulated, and the problems of thrombosis and restenosis of cardiovascular stents in implant interventional surgery are solved, anticoagulation and in situ endothelialization are achieved, and the Cost and improves results.
Patent Information
- Application Number
- CN202411110012.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-14
AI Technical Summary
Existing cardiovascular stents are prone to thrombosis and restenosis during implant interventional surgery. The existing anticoagulant and cell-selective surface design is complex and costly, and bioactive molecules are prone to inactivation, which increases sterilization and storage costs.
Through substrate activation and carbon-carbon double bond silicone modification, anti-fouling molecules such as methoxy polyethylene glycol sulfhydryl, thiol modified poly(2-methyl-2-oxazoline) are grafted to regulate the density of anti-fouling molecules. , realize anticoagulant and in situ endothelialization functions, support endothelial cell adhesion and inhibit smooth muscle cell adhesion.
It achieves a more stable and long-term in situ endothelial function, reduces preparation costs, provides excellent anticoagulation and anti-restenosis effects, and is suitable for implantable interventional medical devices such as cardiovascular stents and heart valves.
Smart Images

Figure CN118615497B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, and in particular to an anti-fouling coating with anti-coagulation and / or in-situ endothelialization functions, and a preparation method and application thereof. Background Art
[0002] Cardiovascular disease is a killer that seriously endangers human life and health. Atherosclerosis, as the most common cardiovascular disease, is one of the root causes of myocardial infarction, stroke, angina pectoris and sudden death. Cardiovascular stents are widely used in implantation and interventional surgery to treat cardiovascular diseases. However, problems such as thrombosis and restenosis in the stent seriously reduce its therapeutic effect. The reason is that during the stent implantation process, the endothelial layer of the vascular intima is destroyed and peeled off, and the stent material itself is easy to adsorb and activate platelets, leading to a coagulation cascade reaction, thereby forming a thrombus; at the same time, the destruction of the endothelial layer exposes the middle layer of the blood vessel, causing smooth muscle cells to migrate from the middle layer of the blood vessel to the endothelial layer and proliferate in large quantities, ultimately leading to excessive proliferation of the new intima, resulting in restenosis. Giving the stent surface a certain degree of anticoagulation and cell selectivity to avoid thrombosis, while inhibiting the excessive proliferation of smooth muscle cells, promoting the coverage of endothelial cells on the surface of the implanted material, and achieving rapid endothelialization to prevent restenosis are the key to improving the success rate of implantation and interventional surgery.
[0003] Existing anticoagulant and cell-selective surfaces are usually prepared by combining anti-fouling backgrounds (such as polyethylene glycol (PEG), zwitterionic polymers, etc.) and bioactive molecules (such as cell growth factors, specific recognition peptides, etc.). Their design and preparation costs are high and the steps are cumbersome. On the other hand, the easy inactivation of bioactive molecules greatly increases the sterilization and storage costs of such products.
[0004] The applicant's previous patent CN101962422A discloses a cardiovascular stent coating material with endothelial cell selectivity and its preparation and application method, which can resist platelet and smooth muscle cell adhesion and specifically promote endothelial cell adhesion, making the coating endothelial cell selective. However, its preparation method involves complex ternary copolymerization and expensive selective polypeptides, and the design and production costs need to be reduced.
[0005] CN110876819A discloses a biomaterial or medical device with an endothelial cell selective gene delivery surface and a preparation method, which can in situ transfect endothelial cells on the surface of the biomaterial or medical device, promote cell proliferation and migration on the surface of the biomaterial or medical device, and achieve rapid endothelialization. However, its preparation process involves expensive bioactive molecules such as streptavidin, polypeptide, and biotin, and the design, production, storage, and sterilization costs also need to be reduced. Summary of the invention
[0006] In view of the problems that existing endothelialized antifouling coatings are insufficiently studied and have a complicated preparation process, the present invention provides a method for preparing an antifouling coating with anticoagulation and / or in situ endothelialization function, covalently grafts antifouling molecules on a substrate, and makes the material have an anticoagulation effect by regulating the density of the antifouling molecules. The in situ endothelialization of the substrate surface is promoted by increasing the adhesion competitiveness of endothelial cells relative to smooth muscle cells.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing an antifouling coating having anticoagulation and / or in situ endothelialization function, comprising the steps of:
[0009] Step 1, activating the substrate;
[0010] Step 2, immersing the activated substrate in a solution containing carbon-carbon double bond siloxane to obtain a modified substrate; or placing the activated substrate and the carbon-carbon double bond siloxane together in a vacuum environment to obtain a modified substrate;
[0011] Step 3, immersing the modified substrate in a mixed solution containing antifouling molecules and an initiator, and obtaining the antifouling coating through photoinitiation or thermal initiation;
[0012] The antifouling molecules include one or more of methoxy polyethylene glycol thiol, thiol-modified poly(2-methyl-2-oxazoline), thiol-modified phosphorylcholine, poly(ethylene glycol) methyl ether methacrylate, 2-methacryloyloxyethyl phosphorylcholine, and poly(2-methyl-2-oxazoline) methyl ether methacrylate;
[0013] The antifouling molecule modification density is 5-200 ng / cm 2 The modification density can be controlled by the molecular weight of the antifouling molecule, the concentration of the antifouling molecule in the reaction solution, the reaction time and the triggering light intensity. In some embodiments, the modification density of the antifouling molecule is 20-180 ng / cm 2 .
[0014] The principle of material surface preparation in the present invention is: a large number of hydroxyl groups exist on the surface of the substrate after activation treatment, and the dehydration condensation between hydroxyl groups and siloxane can be used to achieve olefin functional modification on the surface of different substrates; then, the double-bond modified substrate is immersed in an antifouling molecule solution, and the chemical anchoring of the antifouling functional molecules on the substrate surface can be quickly achieved through the reaction of olefins and antifouling molecules, thereby preparing a stable functional material surface; the inventor unexpectedly discovered that by regulating the density of antifouling molecules, the material surface can have both anticoagulant effect and the function of promoting in situ endothelialization, while supporting endothelial cell adhesion, it can prevent smooth muscle cells from adhering, and improve the in situ endothelialization effect. The coating has a more stable and long-lasting in situ endothelialization function, and can be used on the surface of a series of implanted medical devices such as cardiovascular stents, heart valves, and heart occluders, providing them with excellent anticoagulant and anti-restenosis effects.
[0015] In some embodiments, when the antifouling molecule is methoxy polyethylene glycol thiol or poly (ethylene glycol) methyl ether methacrylate, the antifouling molecule modification density is 30-120 ng / cm 2 ; The modification density is based on the result of fluorescence quantification; preferably, the modification density of the antifouling molecule is 90-110 ng / cm 2 If the modification density is too low, the anti-fouling property of the material surface is insufficient, which will lead to indiscriminate cell adhesion. If the modification density is too high, the anti-fouling property of the material surface is too strong, which will indiscriminately resist the adhesion of all cells. When the modification density is controlled within an appropriate range, the material surface will selectively support the adhesion and growth of endothelial cells by specifically resisting the adhesion of smooth muscle cells, thereby improving the endothelialization effect.
[0016] In some embodiments, when the antifouling molecule is thiol-modified poly(2-methyl-2-oxazoline) or poly(2-methyl-2-oxazoline) methyl ether methacrylate, the antifouling molecule modification density is 50-200 ng / cm 2 ; Preferably, the antifouling molecule modification density is 120-170 ng / cm 2 .
[0017] In some embodiments, when the antifouling molecule is thiol-modified phosphorylcholine or 2-methacryloyloxyethyl phosphorylcholine, the modification density of the antifouling molecule is 5-50 ng / cm 2 Preferably, the density of antifouling molecule modification is 30-50 ng / cm 2 .
[0018] Preferably, the antifouling molecule is methoxy polyethylene glycol thiol, because compared with the other two molecules, methoxy polyethylene glycol thiol is cheaper and has more stable biological functions.
[0019] In some embodiments, the molecular weight of the antifouling molecule is 500-5000; too high a molecular weight will make it difficult to control the grafting density of the antifouling molecule, while too low a molecular weight cannot provide effective antifouling performance for the material surface.
[0020] Preferably, the molecular weight of the antifouling molecule is 1000-3000.
[0021] In some embodiments, the mass concentration of the antifouling molecules in the mixed solution of step 3 is 0.001 mg / mL to 400 mg / mL. Preferably, the mass concentration of the antifouling molecules is 5-20 mg / mL. Too high a concentration will make it difficult to control the grafting density of the antifouling molecules, while too low a concentration will not provide effective antifouling performance for the material surface.
[0022] In some embodiments, the carbon-carbon double bond-containing siloxane includes at least one of 3-(methacryloyloxy)propyltrimethoxysilane, allyltrimethoxysilane, methylvinyldichlorosilane, allyltrichlorosilane, and octyltrichlorosilane;
[0023] Preferably, the carbon-carbon double bond-containing siloxane is 3-(methacryloyloxy)propyltrimethoxysilane.
[0024] In some embodiments, the solvent of the solution of the carbon-carbon double bond siloxane includes at least one of toluene, anhydrous ethanol, and anhydrous methanol, preferably toluene; wherein the volume fraction of the carbon-carbon double bond siloxane is 0.01% to 10%, preferably 0.1-0.5%.
[0025] In some embodiments, the initiator comprises a thermal initiator or a photoinitiator;
[0026] The photoinitiator includes one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylpropanone;
[0027] The thermal initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, and tert-butyryl peroxide.
[0028] In some embodiments, the light-induced ultraviolet light intensity is 1 to 400 mW / cm 2 , the reaction time is 1s~60min.
[0029] In some embodiments, the thermal initiation reaction temperature is 1 to 100° C., and the reaction time is 1 s to 60 min.
[0030] In some embodiments, the mass concentration of the initiator in the mixed solution of step 3 is 0.001 mg / mL to 400 mg / mL.
[0031] In some embodiments, the solvent in step 3 includes at least one of deionized water, PBS buffer, HEPES buffer, Tris buffer, MES buffer, acetate buffer, carbonate buffer, toluene, anhydrous ethanol, and methanol.
[0032] The activation in step 1 includes plasma activation treatment, ozone activation treatment or piranha solution immersion activation treatment;
[0033] In some embodiments, the frequency of the plasma treatment machine is 40KHz to 13.56MHz; the plasma activation treatment or ozone activation treatment time is 10s to 60min; the piranha solution is a mixture of concentrated sulfuric acid and 30% hydrogen peroxide, wherein the ratio of concentrated sulfuric acid to 30% hydrogen peroxide is 19:1 to 1:19, and the immersion time is 1 to 120 min.
[0034] The material of the substrate includes any one of the following materials:
[0035] (1) Metal materials: any one of stainless steel, titanium and its alloys, cobalt-based alloys, nickel-titanium alloys, magnesium and its alloys, zinc and its alloys, iron and its alloys; or,
[0036] (2) Inorganic materials: any one of glass, silicon dioxide, titanium dioxide, carbon materials, silicon, and titanium nitride; or,
[0037] (3) Polymer materials: any one of polyester, polyvinyl alcohol, polyethylene, polytetrafluoroethylene, polyvinyl chloride, polystyrene, poly-4-vinylpyridine, polyurethane, polypropylene, polyamide, polycarbonate, polyacrylonitrile, polyacrylate, polymethacrylate, polyetheretherketone, silicone rubber, polylactic acid, polyglycolide, polylactide, polycaprolactone, or their copolymers or derivatives;
[0038] Preferably, the substrate is made of at least one of stainless steel, nickel-titanium alloy, magnesium alloy, glass, and polylactic acid.
[0039] In some embodiments, in step 2, when the substrate is a solvent-intolerant material, a vapor deposition method is used to prepare a modified substrate, specifically comprising: placing the activated substrate and a carbon-carbon double bond-containing siloxane in a vacuum environment at a temperature of 15-40° C. for more than 1 hour to obtain a modified substrate.
[0040] In some embodiments, in step 2, when the substrate is a solvent-resistant material, a liquid phase solution immersion method is used to prepare a modified substrate, specifically comprising: immersing the activated substrate in a solution containing carbon-carbon double bond siloxane to obtain a modified substrate, the immersion time is 0.1-72 hours, and the temperature is 0-50° C. Preferably, the immersion time is 6-24 hours, and more preferably 8-15 hours.
[0041] Preferably, the modified substrate in step 2 is washed, soaked and dried with a solvent, anhydrous ethanol, ultrapure water and anhydrous ethanol in sequence, the oven temperature is 20° C. to 75° C., and the drying time is 1 min to 72 h.
[0042] In the prior art, it is usually necessary to design complex bioactive molecules to promote the adhesion, proliferation and migration of endothelial cells on the surface of biomaterials or devices to achieve endothelialization. However, it has the disadvantages of high molecular design cost, difficulty in determining the effect, limited source of raw materials, and high price. The present invention also provides an anti-fouling coating with anti-coagulation and / or in situ endothelialization function prepared according to the preparation method. The preparation source of the anti-fouling coating is simple, no synthesis is required, and the preparation conditions are mild and easy to operate. By regulating the density of the anti-fouling molecules, the anti-coagulation and / or in situ endothelialization effect can be effectively achieved.
[0043] The present invention also provides the use of the anti-fouling coating in the preparation of anti-coagulation and / or in situ endothelialization functional materials. The present invention unexpectedly discovered that by optimizing the grafting density of anti-fouling molecules, it is possible to effectively inhibit the adhesion and activation of platelets on the surface of the material and inhibit the occurrence of coagulation reactions; at the same time, it can selectively support the adhesion, proliferation and migration of endothelial cells, while inhibiting the adhesion, proliferation and migration of smooth muscle cells, so that the growth rate of endothelial cells on the coating surface is much greater than that of smooth muscle cells, thereby promoting the rapid formation of a complete endothelial layer on the coating surface, inhibiting the excessive proliferation of smooth muscle cells, and avoiding the occurrence of postoperative restenosis. Therefore, the coating can be used on the surface of a series of implantable medical devices such as cardiovascular stents, heart valves, and heart occluders, providing them with excellent anti-coagulation and / or in situ endothelialization effects.
[0044] The coating has one of the following functions:
[0045] (1) Inhibit platelet adhesion and activation;
[0046] (2) Inhibit coagulation reaction;
[0047] (3) Inhibit smooth muscle cell adhesion, proliferation and migration;
[0048] (4) Support endothelial cell adhesion, proliferation and migration;
[0049] (5) Promote in situ endothelialization.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The present invention grafts antifouling functional molecules after substrate activation and double-bond siloxane modification, and unexpectedly finds that by regulating the grafting density of antifouling molecules, it can support the selective adhesion of endothelial cells and inhibit the adhesion of smooth muscle cells, greatly promoting the in situ endothelialization of the substrate surface. The preparation method of the antifouling coating is simple, and the antifouling molecules that promote endothelialization do not require complex synthesis. It can be used on the surface of a series of implantable medical devices such as cardiovascular stents, heart valves, and heart occluders, providing them with excellent anticoagulation and / or in situ endothelialization effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0053] Figure 1 The water contact angles of the coatings of Examples 1-4, Comparative Examples 1-2 and the untreated glass surface.
[0054] Figure 2 It is the grafting density of the coating functional molecules in Examples 1-4 and Comparative Examples 1-2.
[0055] Figure 3 It is a statistical diagram of the adhesion density of endothelial cells / smooth muscle cells on the coating surfaces of Examples 1-4 and Comparative Examples 1-2.
[0056] Figure 4 The figure is a statistical diagram of the proliferation density of endothelial cells / smooth muscle cells on the coating of Example 1 and the untreated glass surface.
[0057] Figure 5 The blood coagulation conditions of the coating of Example 1 and the untreated glass surface are shown in FIG. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0059] The raw materials used in the following specific embodiments are all purchased from the market.
[0060] Example 1
[0061] Preparation of representative antifouling coatings with anticoagulation and / or in situ endothelialization functions:
[0062] (1) Surface activation treatment of materials: Place the glass piece in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 minutes; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 minutes; take out the cleaned glass piece, and 2 Blow dry, place in piranha solution (concentrated sulfuric acid: hydrogen peroxide = 7:3) for surface activation treatment for 15 min;
[0063] (2) Olefin modification of substrate: 0.5 vol% 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, and the activated glass sheet was immersed in the obtained silane solution at room temperature for 12 h, and then washed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, and then washed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0064] (3) Antifouling functional molecule modification of substrate: 2.5 mg / mL methoxypolyethylene glycol thiol (molecular weight 1000) and 0.5 mg / mL 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution and exposed to ultraviolet light at 30 mW / cm 2 After irradiation for 15 seconds, the sample was washed with ultrapure water for 3 times, each time for 5 minutes, and dried with nitrogen to obtain the antifouling coating Sample 1 having anticoagulation and / or in situ endothelialization function.
[0065] Example 2
[0066] Preparation of representative antifouling coatings with anticoagulation and / or in situ endothelialization functions:
[0067] (1) Surface activation treatment of materials: Place the glass piece in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 minutes; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 minutes; take out the cleaned glass piece at room temperature, 2 Blow dry, place in piranha solution (concentrated sulfuric acid: hydrogen peroxide = 7:3) for 15 min to modify the surface hydrophilicity;
[0068] (2) Olefin modification of substrate: 0.5 vol% 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, and the activated glass sheet was immersed in the obtained silane solution at room temperature for 12 h, and then washed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, and then washed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0069] (3) Antifouling functional molecular modification of substrates: 2.5 mg / mL of methoxypolyethylene glycol thiol (molecular weight 2000) and 0.1 mg / mL of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution. The UV light was 3.4 mW / cm 2 After irradiation for 15 seconds, the sample was washed with ultrapure water for 3 times, each time for 5 minutes, and dried with nitrogen to obtain the antifouling coating Sample 2 having anticoagulation and / or in situ endothelialization function.
[0070] Example 3
[0071] Preparation of representative antifouling coatings with anticoagulation and / or in situ endothelialization functions:
[0072] (1) Surface activation treatment of materials: Place the glass piece in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 minutes; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 minutes; take out the cleaned glass piece, and 2 Blow dry, place in piranha solution (concentrated sulfuric acid: hydrogen peroxide = 7:3) for surface activation treatment for 15 min;
[0073] (2) Olefin modification of substrate: 0.5 vol% 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, and the activated glass sheet was immersed in the obtained silane solution at room temperature for 12 h, and then washed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, and then washed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0074] (3) Antifouling functional molecule modification of substrate: 5 mg / mL of thiol-modified poly(2-methyl-2-oxazoline) (molecular weight 2000) and 0.5 mg / mL of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution and exposed to ultraviolet light at 30 mW / cm 2After irradiation for 15 seconds, the sample was washed with ultrapure water for 3 times, each time for 5 minutes, and dried with nitrogen to obtain the antifouling coating Sample 3 having anticoagulation and / or in situ endothelialization function.
[0075] Example 4
[0076] Preparation of representative antifouling coatings with anticoagulation and / or in situ endothelialization functions:
[0077] (1) Surface activation treatment of materials: Place the glass piece in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 minutes; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 minutes; take out the cleaned glass piece, and 2 Blow dry, place in piranha solution (concentrated sulfuric acid: hydrogen peroxide = 7:3) for surface activation treatment for 15 min;
[0078] (2) Olefin modification of substrate: 0.5 vol% 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, and the activated glass sheet was immersed in the obtained silane solution at room temperature for 12 h, and then washed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, and then washed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0079] (3) Antifouling functional molecule modification of substrate: 2.5 mg / mL of thiol-modified phosphorylcholine and 0.5 mg / mL of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution. The ultraviolet light was 30 mW / cm 2 After irradiation for 15 seconds, the sample was washed with ultrapure water for 3 times, each time for 5 minutes, and dried with nitrogen to obtain the antifouling coating Sample 4 having anticoagulation and / or in situ endothelialization function.
[0080] Example 5
[0081] Preparation of representative antifouling coatings with anticoagulation and / or in situ endothelialization functions:
[0082] (1) Surface activation treatment of materials: Place a stainless steel sheet (2 cm × 2 cm × 1 mm) in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 min; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 min; take out the cleaned glass sheet, and 2 After drying, the surface was placed in a plasma cleaning machine and treated at a frequency of 13.56 MHz for 3 min to perform surface hydrophilic modification;
[0083] (2) Olefin modification of substrate: a stainless steel sheet and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were placed in a vacuum environment for 12 h, then rinsed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, then rinsed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0084] (3) Antifouling functional molecular modification of substrates: 2.5 mg / mL of poly(ethylene glycol) methyl ether methacrylate (molecular weight 2000) and 0.1 mg / mL of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution and exposed to ultraviolet light at 60 mW / cm 2 After irradiation for 15 seconds, the sample was washed with ultrapure water for 3 times, each time for 5 minutes, and dried with nitrogen to obtain the antifouling coating Sample 5 having anticoagulation and / or in situ endothelialization function.
[0085] Comparative Example 1
[0086] Modifying material surfaces using extremely low density functional molecules
[0087] (1) Surface activation treatment of materials: Place the glass piece in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 minutes; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 minutes; take out the cleaned glass piece, and 2 Blow dry, place in piranha solution (concentrated sulfuric acid: hydrogen peroxide = 7:3) for 15 min to modify the surface hydrophilicity;
[0088] (2) Olefin modification of substrate: 0.5 vol% 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, and the activated glass sheet was immersed in the obtained silane solution at room temperature for 12 h, and then washed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, and then washed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0089] (3) Antifouling functional molecule modification of substrate: 0.01 mg / mL of thiol-modified polyethylene glycol (molecular weight 1000) and 0.01 / mL of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution. The ultraviolet light was 0.04 mW / cm 2 After irradiation for 1 second, the sample was washed with ultrapure water for 3 times, 5 minutes each time, and dried with nitrogen to obtain Control 1, a material surface modified with extremely low density functional molecules.
[0090] Comparative Example 2
[0091] Modify the surface of materials using extremely high density of functional molecules
[0092] (1) Surface activation treatment of materials: Place the glass piece in a beaker, add sufficient ultrapure water, and place it in an ultrasonic cleaning machine for 5 minutes; pour out the ultrapure water in the beaker, add anhydrous ethanol, and ultrasonicate for 5 minutes; take out the cleaned glass piece, and 2 Blow dry, place in piranha solution (concentrated sulfuric acid: hydrogen peroxide = 7:3) for 15 min to modify the surface hydrophilicity;
[0093] (2) Olefin modification of substrate: 0.5 vol% 3-(methacryloyloxy)propyltrimethoxysilane was dissolved in toluene, and the activated glass sheet was immersed in the obtained silane solution at room temperature for 12 h, and then washed with toluene, anhydrous ethanol, and ultrapure water twice, each time for 5 min, and then washed with anhydrous ethanol once, and placed in an oven for drying at 60 °C for 1 h.
[0094] (3) Antifouling functional molecule modification of substrate: 10 mg / mL of thiol-modified polyethylene glycol (molecular weight 5000) and 0.05 / mL of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone were dissolved in ultrapure water, and the olefin-modified glass slide was immersed in the resulting solution and exposed to ultraviolet light at 80 mW / cm 2 After irradiation for 10 min, the sample was washed with ultrapure water for 3 times, 5 min each time, and dried with nitrogen to obtain Control 2, a material surface modified with extremely high density of functional molecules.
[0095] Application Examples
[0096] 1. Surface characterization of representative materials
[0097] The hydrophilicity of the surface was checked by using a contact angle goniometer (Dataphysics OCA 20). As the grafting density and molecular weight of the antifouling functional molecule (PEG) increased, the water contact angle on the surface of the material decreased to varying degrees. Figure 1 It can be seen that compared with the glass substrate modified with double bonds but without antifouling functional molecules, the water contact angles of the comparative examples and the examples have decreased to varying degrees, indicating that the density and molecular weight of the functional molecules grafted on the surface are different. The density of the antifouling functional molecules on the surface of the comparative example Control 1 is lower, the density of the antifouling functional molecules on the surface of the comparative example Control 2 is higher, and the density of the antifouling functional molecules on the surface of the examples Samples 1-4 is between the above two.
[0098] Determine the grafting density of functional molecules by fluorescence quantification: label the functional molecules with the fluorescent molecule FITC, measure the fluorescence intensity of the sample surface after the functional molecules are grafted, and calculate the functional molecule density on the sample surface by combining the "functional molecule density-fluorescence intensity standard curve". Figure 2 As can be seen in the figure, the functional molecule grafting density of Control 1 and Control 2, and Examples Sample 1, Sample 2, Sample 3, and Sample 4 is 4.2 ng / cm 2 、770.7 ng / cm 2 , 104.2 ng / cm 2 , 91.5 ng / cm 2 , 152.4 ng / cm 2 and 43.3ng / cm 2 .
[0099] 2. In vitro cell adhesion of representative antifouling coatings with anticoagulation and / or in situ endothelialization functions
[0100] Cell culture: The endothelial cells (EC) and smooth muscle cells (SMC) used were human umbilical vein endothelial cells (HUVEC) and human umbilical artery smooth muscle cells (HUASMC), respectively. Both were isolated from fresh human umbilical cord samples. The acquisition of umbilical cord samples was approved by the local medical ethics committee. The culture medium for EC was EC medium supplemented with 10% fetal bovine serum (FBS), 20μg / mL endothelial cell growth factor (ECGS), and 1%UI / mL penicillin-streptomycin. The culture medium for SMC was SMC medium supplemented with 10% FBS, 20μg / mL smooth muscle cell growth factor (SMCGS), and 1%UI / mL penicillin-streptomycin. Both EC and SMC were cultured at 37°C with CO 2 The cells were cultured in an incubator (Series II, FormaScientific Inc.) with a 5% concentration of 5%. The cells were cultured every two to three days, and the number of cell generations used was between 3 and 8. Cell experiments could be performed when the cells filled 80-90% of the culture dish.
[0101] Cell adhesion assay: EC and SMC were stained with CellTracker™ Orange CMTMR (5-(and-6)-(((4-chloromethyl)benzoyl)amino)tetramethylrhodamine) (1μg / mL) and CellTracker™ Green CMFDA (5-chloromethylfluorescein diacetate) (1μg / mL) for 30 min. Then, 2 mL of trypsin was added to the EC and SMC culture dishes, digested for 2 min, and 2 mL of culture medium was added for neutralization. The cells were detached from the wall by pipetting, and the cell suspension was added to a 15 mL centrifuge tube and centrifuged (1000 rpm, 5 min). EC culture medium was added and mixed to prepare a cell suspension. The cells were counted, diluted, and mixed using a hemocytometer. A 2 cm × 2 cm sample material was placed in a 6-well plate at 100 cells / mm 2 The cells were planted at a density of half (EC and half SMC) (2.5 mL culture medium per well) and incubated in an incubator for 4 hours. The cells were then fixed with 4% paraformaldehyde, and cell fluorescence images were taken with a fluorescence microscope. The number of cells on each sample was counted using ImageJ software. Three parallel samples were tested for each group of samples, and the average value was taken.
[0102] from Figure 3 It can be seen that both EC and SMC adhered in large quantities on the surface of Comparative Example 1, and its EC / SMC ratio was close to 1, indicating that the adhesion of the two cells on the glass surface was similar; the adhesion of EC and SMC on the surface of Comparative Example 2 decreased significantly, and its EC / SMC ratio was also close to 1. However, on the surfaces of Examples 1-4, the EC adhesion decreased to a certain extent compared with the glass surface, but the SMC decreased more, and the EC / SMC ratio was about 10, showing extremely excellent EC selective adhesion.
[0103] Cell proliferation assay: EC and SMC were stained with CellTracker™ Orange CMTMR dye (5-(and-6)-(((4-chloromethyl)benzoyl)amino)tetramethylrhodamine) (1 μg / mL) and CellTracker™ Green CMFDA dye (5-chloromethylfluorescein diacetate) (1 μg / mL) for one hour. Then, 2 mL of trypsin was added to the EC and SMC culture dishes respectively, digested for 2 min, 2 mL of culture medium was added for neutralization, and the cells were detached by pipetting with a dropper. The cell suspension was added to a 15 mL centrifuge tube and centrifuged (1000 rpm for 5 min), and the culture medium was added to mix to prepare a cell suspension. The cells were counted using a hemocytometer, diluted, and mixed. The samples were placed in a 24-well plate at 100 cells / mm 2 Cells were seeded at a density of half (EC and half SMC) (1 mL culture medium per well), incubated in the incubator for 4 hours / 1 day / 2 days / 3 days, and then fixed with 4% paraformaldehyde. Cell fluorescence images were scanned with a fluorescence microscope, and the number of cells on each sample was counted using ImageJ software. Three parallel samples were tested for each group of samples, and the average value was taken.
[0104] from Figure 4 It can be seen that the initial adhesion amount of EC and SMC on the glass surface at 4 hours is similar, and in the subsequent proliferation process, the growth rates of the two are also similar, so the cell density of the two always grows synchronously and remains at a similar level; while the initial adhesion amount of EC on the surface of Example 1 at 4 hours is much greater than that of SMC. Therefore, in the subsequent proliferation process, EC grows rapidly, while the growth rate of SMC is very slow, which makes the cell density gap between the two continue to increase, and finally a complete endothelial layer can be quickly formed, indicating that the chemically grafted antifouling molecules have excellent in situ endothelialization function.
[0105] 3. Chandler Ring Experiment
[0106] Add 5 mL of saline (0.9 wt% NaCl solution) to the Chandler ring, connect the two ends of the tube with an interface, fix it on a rotating rack, and rinse it in a 37°C water bath at a speed of 10 rpm for 15 minutes; then pour out the saline, add 5 mL of fresh rabbit blood and 250 μL of 0.15 mol / L CaCl 2 The solution was added, the sample was put in and fixed, and after sealing, it was placed on a rotating rack, in a 37°C water bath at a rotation speed of 10 rpm for 15 min; finally, the sample was taken out, washed with ultrapure water, and photographed to record the surface coagulation situation.
[0107] from Figure 5 It can be seen that there are a lot of blood clots on the glass surface that cannot be washed away, while almost no obvious blood clots are observed on the surface of Example 1, indicating that it has excellent anti-coagulation effect.
Claims
1. Application of an antifouling coating in the preparation of anticoagulation and in situ endothelialization functional materials, characterized in that: The coating has the function of inhibiting the adhesion, proliferation and migration of smooth muscle cells, and at the same time has the function of supporting the adhesion, proliferation and migration of endothelial cells, and also has one of the following functions: (1) Inhibit platelet adhesion and activation; (2) Inhibit coagulation reaction; (3) Promote in situ endothelialization; The method for preparing the antifouling coating comprises the steps of: Step 1, activating the substrate; Step 2, immersing the activated substrate in a solution containing carbon-carbon double bond siloxane to obtain a modified substrate; or placing the activated substrate and the carbon-carbon double bond-containing siloxane together in a vacuum environment to obtain a modified substrate; Step 3, immersing the modified substrate in a mixed solution containing antifouling molecules and an initiator, and obtaining the antifouling coating through photoinitiation or thermal initiation; The antifouling molecules include one or more of methoxy polyethylene glycol thiol, thiol-modified poly(2-methyl-2-oxazoline), thiol-modified phosphorylcholine, poly(ethylene glycol) methyl ether methacrylate, 2-methacryloyloxyethyl phosphorylcholine, and poly(2-methyl-2-oxazoline) methyl ether methacrylate; When the antifouling molecule is methoxy polyethylene glycol thiol or poly (ethylene glycol) methyl ether methacrylate, the antifouling molecule modification density is 90-110 ng / cm 2 ; When the antifouling molecule is thiol-modified poly(2-methyl-2-oxazoline) or poly(2-methyl-2-oxazoline) methyl ether methacrylate, the antifouling molecule modification density is 120-170 ng / cm 2 ; When the antifouling molecule is thiol-modified phosphorylcholine or 2-methacryloyloxyethyl phosphorylcholine, the modification density of the antifouling molecule is 30-50 ng / cm 2 ; The molecular weight of the antifouling molecule is 1000-3000; The mass concentration of the antifouling molecule in the mixed solution of step 3 is 5-20 mg / mL.
2. The use according to claim 1, characterized in that: The carbon-carbon double bond-containing siloxane includes at least one of 3-(methacryloyloxy)propyltrimethoxysilane, allyltrimethoxysilane, methylvinyldichlorosilane, allyltrichlorosilane, and octyltrichlorosilane; The solvent of the solution of the carbon-carbon double bond siloxane includes at least one of toluene, anhydrous ethanol and anhydrous methanol, wherein the volume fraction of the carbon-carbon double bond siloxane is 0.01% to 10%.
3. The use according to claim 1, characterized in that: The initiator includes a thermal initiator or a photoinitiator; The photoinitiator includes one or more of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-hydroxy-2-methyl-1-phenylpropanone; The thermal initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, and tert-butyryl peroxide; And / or, the light-induced ultraviolet light intensity is 1-400 mW / cm 2 , reaction time is 1s~60min; And / or, the thermal initiation reaction temperature is 1-100° C., and the reaction time is 1 s-60 min.
4. The use according to claim 1, characterized in that: The mass concentration of the initiator in the mixed solution of step 3 is 0.001 mg / mL to 400 mg / mL; And / or, in step 3, the solvent includes at least one of deionized water, PBS buffer, HEPES buffer, Tris buffer, MES buffer, acetate buffer, carbonate buffer, toluene, anhydrous ethanol, and methanol.
5. The use according to claim 1, characterized in that: The activation in step 1 includes plasma activation treatment, ozone activation treatment or piranha solution immersion activation treatment; The frequency of the plasma treatment machine is 40KHz to 13.56MHz; the plasma activation treatment or ozone activation treatment time is 10s to 60min; the ratio of concentrated sulfuric acid and 30% hydrogen peroxide in the piranha solution is 19:1 to 1:19, and the immersion time is 1 to 120min; And / or, the material of the substrate includes any one of the following materials: (1) Metal materials: any one of stainless steel, titanium and its alloys, cobalt-based alloys, nickel-titanium alloys, magnesium and its alloys, zinc and its alloys, iron and its alloys; or, (2) Inorganic materials: any one of glass, silicon dioxide, titanium dioxide, carbon materials, silicon, and titanium nitride; or, (3) Polymer materials: any one of polyester, polyvinyl alcohol, polyethylene, polytetrafluoroethylene, polyvinyl chloride, polystyrene, poly-4-vinylpyridine, polyurethane, polypropylene, polyamide, polycarbonate, polyacrylonitrile, polyacrylate, polymethacrylate, polyetheretherketone, silicone rubber, polylactic acid, polyglycolide, polylactide, polycaprolactone, or their copolymers or derivatives; And / or, in step 2, when the substrate is a solvent-intolerant material, a vapor deposition method is used to prepare a modified substrate, specifically comprising: placing the activated substrate and the carbon-carbon double bond-containing siloxane in a vacuum environment at a temperature of 15-40° C. for more than 1 hour to obtain a modified substrate; And / or, in step 2, when the substrate is a solvent-resistant material, a liquid phase solution immersion method is used to prepare the modified substrate, specifically comprising: immersing the activated substrate in a solution containing carbon-carbon double bond siloxane to obtain a modified substrate, the immersion time is 0.1-72h, and the temperature is 0-50°C.
Citation Information
Patent Citations
Cardiovascular stent coating material with endothelial cell selectivity and preparation and application method thereof
CN101962422A
Biomaterial or medical device with endothelial cell selective gene delivery surface and preparation method thereof
CN110876819A
Non-fouling, anti-microbial, anti-thrombogenic graft-from compositions
CN102307955A
Durable and stable hydrophilic dirt-resisting coating for intraocular lens and preparation method of durable and stable hydrophilic dirt-resisting coating
CN111790006A
Polyelectrolyte hydrogel coating with super-strong substrate adhesion performance and preparation method of polyelectrolyte hydrogel coating
CN113842507A
